2012
DOI: 10.1089/cbr.2011.1156
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Distribution of 131I and 125I Dual-Labeled Gelatin Microspheres After Implantation into Rabbit Liver

Abstract: (131)I-(125)I-GMS can be retained long term in the injection site. Due to the advantages of combining two radionuclides, (131)I-(125)I-GMS may be a safe and effective choice for cancer brachytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…At 35 days after injection, there were still large number of microspheres within the tumors (Figure  5D). In our previous studies, the microspheres which were injected into the parenchyma of liver of rabbits could still be observed by histological method even 32 days( 4 half-lives) after injection [27,28]. Perhaps much more effort is needed to retard the degradation of the microspheres, thus minimizing the de-labeling of radioiodine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 35 days after injection, there were still large number of microspheres within the tumors (Figure  5D). In our previous studies, the microspheres which were injected into the parenchyma of liver of rabbits could still be observed by histological method even 32 days( 4 half-lives) after injection [27,28]. Perhaps much more effort is needed to retard the degradation of the microspheres, thus minimizing the de-labeling of radioiodine.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin microspheres are a type of derivative of collagen with a good level of biocompatibility, and they can be labeled with a high concentration of radioiodine. In our previous studies, we injected 131 I labeled gelatin microspheres and 131 I, 125 I dual-labeled gelatin microspheres into the liver parenchyma of rabbits, and we found that the injected microspheres mainly accumulated around the injection site, and the small amount of de-labeled radioiodine did not cause severe damage to other tissues [27,28]. In the present study, we evaluated use of 131 I-GMSs as an effective radiopharmaceutical for the treatment of transplanted human breast cancer (MCF-7) in nude mice following intratumoral injections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, glass-based radioactive microspheres are prone to reflux, poor distribution, and ectopic embolism, which will increase the incidence of radioactivity damage to nontarget tissues . Therefore, biodegradable polymers, such as albumin, gelatin, chitosan, and polylactic acid have been widely applied to develop radioactive microspheres. Especially, biomass-derived radioactive microspheres take advantage of abundant resources, good biocompatibility, and renewable and environmentally friendly properties, which are beneficial for utilization in HCC treatment. However, the low radionuclide labeling rate, poor labeling stability, and the residual chemical reagents in the preparation of radioactive microspheres are still the crucial challenges related to the development of biodegradable radioactive microspheres .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 131 iodine in GM eluted more slowly and have a longer stagnation time in liver tumors than 131 iodine metuximab injection, which is likely to achieve better radiotherapy results. After demonstrating safety in animal experiments (18), we carried out a preliminary trial of TACE with 131 iodine-doxorubicineluting gelatin microspheres ( 131 I-DEM) in 11 patients with unresectable HCC. We present the following article in accordance with the STROBE reporting checklist (available at http://dx.doi.org/10.21037/jgo-21-105).…”
Section: Introductionmentioning
confidence: 99%